KIAA1199 (CEMIP) regulates adipogenesis and whole-body energy metabolism - Li Chen; Kaikai Shi; Nicholas Ditzel; Weimin Qiu; Michaela Tencerova; Louise Himmelstrup Dreyer Nielsen; Florence Figeac; Alexander Rauch; Yuhang Liu; Jiuyuan Tao; Veronika Sramkova; Lenka Rossmeislova; et al. (Bone Research)
Abstract An increasing number of studies have characterized the bone as an endocrine organ, and that bone secreted factors may not only regulate local bone remodeling, but also other tissues and whole-body metabolic functions. The precise nature of these regulatory factors and their roles at bridging the bone, bone marrow adipose tissue, extramedullary body fat and whole-body energy homeostasis are being explored. In this study, we report that KIAA1199, a secreted factor produced from bone and bone marrow, previously described as an inhibitor of bone formation, also plays a role at promoting adipogenesis. KIAA1199-deficient mice exhibit reduced bone marrow adipose tissue, subcutaneous and visceral fat tissue mass, blood cholesterol, triglycerides, free fatty acids and glycerol, as well as improved insulin sensitivity in skeletal muscle, liver and fat. Moreover, these mice are protected from the detrimental effects of high-fat diet feeding, with decreased obesity, lower blood glucose and glucose tolerance, as well as decreased adipose tissue inflammation, insulin resistance and hepatic steatosis. In human studies, plasma levels of KIAA1199 or its expression levels in adipose tissue are positively correlated with insulin resistance and blood levels of cholesterol, triglycerides, free fatty acids, glycerol, fasting glucose and HOMA-IR. Mechanistically, KIAA1199 mediates its effects on adipogenesis through modulating osteopontin-integrin and AKT / ERK signaling. These findings provide evidence for the role of bone secreted factors on coupling bone, fat and whole-body energy homeostasis.